Actor Network in The Prevention of Narcotics Trafficking In Class IIB Correctional Institution Gunung Sugih - Meitisa Vanya Simanjuntak (Jurnal Indonesia Sosial Teknologi, 2025)
Narcotics crime ranks as the second-highest crime in Indonesia, and this is deeply concerning due to its potential negative impact on the future generations of the nation. In Indonesia, drug smuggling and distribution occur not only within the community but even within prisons and detention centers, which serve as places of criminal activity for suspects involved in drug trafficking and abuse. In this case, Class IIB Gunung Sugih Penitentiary has made efforts toward preventive measures to counteract the spread and distribution of narcotics within the facility. This research adopts a qualitative method with a descriptive research design, collecting information directly from key informants, including the Head of Class IIB Gunung Sugih Penitentiary, the Head of Penitentiary Security Unit, the Head of Security and Order Section, and the Main Gate Security Officers (P2U). Applying Actor-Network Theory, the research findings reveal that the network of actors involved in drug trafficking prevention at Class IIB Gunung Sugih Penitentiary consists of the following stages: Punctualization, Translation, Problematization, Interessement, Enrollment, Speaker/Delegate Representative, and Irreversibility. All officers at Class IIB Gunung Sugih Penitentiary play crucial roles in drug trafficking prevention efforts. These prevention efforts include systematic inspection, searches, checks, and inspections.